Impact of pulmonary valve replacement on ventricular arrhythmias in patients with tetralogy of Fallot. (24th May 2021) - Bessiere, F; Gardey, K; Duthoit, G; Koutbi, L; Labombarda, F; Marquie, C; Gourraud, JB; Mondoly, P; Bordachar, P; Martins, R; Pasquie, JL; Combes, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): INSERM - French Society of Cardiology OnBehalf: DAIT4F Investigators Background: Sudden cardiac death is a major cause of death in tetralogy of Fallot (TOF) and right ventricular overload is commonly considered as a potential trigger for ventricular arrhythmias. Purpose: We aimed to assess the impact of pulmonary valve replacement (PVR) on ventricular arrhythmias burden using a population of TOF patients with continuous cardiac monitoring by implantable cardioverter defibrillator (ICD). Methods: Nationwide French registry including all TOF patients with an ICD. Survival data with recurrent events were used to compare the burden of appropriate ICD therapies before and after PVR in patients who underwent PVR over the study period. Results: A total of 165 patients (mean age 42.2 ± 13.3 years, 70.1% males) were included from 40 centers. Over a median (IQR) follow-up period of 6.8 (2.5-11.4) years, 26 (15.8%) patients underwent PVR. Among those patients, 18 (69.2%) experienced at least one appropriate ICD therapy. When considering all ICD therapies delivered before (n = 62) and after (n = 16) PVR, the burden of ICD appropriate therapies was significantly lower after PVR (HR 0.21, 95%CI 0.08-0.56, p = 0.002). In the overall cohort, PVR before ICD implantation was also independently associated with a lower risk of appropriate ICD therapy in primary prevention patients (HR 0.29, 95%CI 0.10-0.89, p = 0.031). Conclusions: In this cohort of high-risk TOF patients implanted with an ICD, the burden of appropriate ICD therapies was significantly reduced after PVR. While optimal indications and timing for PVR are debated, these findings suggest the importance of considering ventricular arrhythmias in the overall making-decision process.